2013
DOI: 10.1016/j.mce.2013.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Differential β-arrestin2 requirements for constitutive and agonist-induced internalization of the CB1 cannabinoid receptor

Abstract: CB 1 cannabinoid receptor (CB 1 R) undergoes both constitutive and agonist-induced internalization, but the underlying mechanisms of these processes and the role of β-arrestins in the regulation of CB 1 R function are not completely understood. In this study, we followed CB 1 R internalization using confocal microscopy and bioluminescence resonance energy transfer measurements in HeLa and Neuro-2a cells. We found that upon activation CB 1 R binds β-arrestin2 (β-arr2), but not β-arrestin1. Furthermore, both the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 59 publications
3
42
1
Order By: Relevance
“…The dissimilarity in the agonist induced and constitutive internalization observed in this study in case of I130N-V2R is not unique among GPCRs, since β-arrestin-dependent, agonist-induced endocytosis and β-arrestin-independent constitutive internalization was introduced earlier (22)(23)(24). It is also notable, that basal internalization is not obviously a consequence of constitutive activity (25).…”
Section: Discussionmentioning
confidence: 56%
“…The dissimilarity in the agonist induced and constitutive internalization observed in this study in case of I130N-V2R is not unique among GPCRs, since β-arrestin-dependent, agonist-induced endocytosis and β-arrestin-independent constitutive internalization was introduced earlier (22)(23)(24). It is also notable, that basal internalization is not obviously a consequence of constitutive activity (25).…”
Section: Discussionmentioning
confidence: 56%
“…4A), raising the question whether the reduced E max value of CB 1 R-AAY in this assay reflects a true loss of agonist-induced G-protein activation, or it is caused merely by the absence of basal activity, while WIN55-induced G-protein activation remains unaffected. However, repeating these experiments in HeLa cells, where basal activity of CB 1 R is minimal (Gyombolai et al 2013), also showed substantially impaired WIN55-induced G-protein activation of CB 1 R-AAY (Supplementary Figure 1, see section on supplementary data given at the end of this article), suggesting that this mutation reduces not only the basal but also the WIN55-induced G o protein activation of CB 1 R. In contrast, CB 1 R-DAA proved to be G-protein-biased, as its b-arr recruitment in response to agonist stimulus was practically absent, but was still able to activate G-proteins, although at a lower level (w70% of the WT CB 1 R). According to our data, plasma membrane expression of this mutant is ca.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, CB 1 R shows basal G-protein activation and constitutive internalization under diverse cellular conditions (Leterrier et al 2006, McDonald et al 2007, Turu et al 2007. Like most other 7TMRs, CB 1 R also recruits b-arr following activation, which leads to the desensitization and internalization of the receptor (Kouznetsova et al 2002, Daigle et al 2008, Gyombolai et al 2013. The binding between b-arrs and CB 1 R is relatively weak, and the affinity of the receptor for b-arr2 (b-arr2) is substantially higher than that for b-arr1 (b-arr1) (Gyombolai et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As typical of G proteins coupled receptors (GPCRs), PAFR activation by PC could be regulated by β-arrestins (McLaughlin et al, 2006;Eckels et al, 2009). β-Arrestins could bind to activated GPCRs and clathrin to promote the clathrin-mediated endocytosis and transcytosis (Shenoy and Lefkowitz, 2011;Gyombolai et al, 2013). The role of β-arrestins in inflammation process has been well known by regulation of chemokine responsiveness (Vroon et al, 2006;Cattaruzza et al, 2013;Porter et al, 2010).…”
Section: Primermentioning
confidence: 99%